Efficiency of alvarado score in diagnosis of acute appendicitis (Annals of Medical Research, 2021)
Aim: Acute appendicitis is the most common cause of abdominal pain resulting in surgery. This study aims to investigate the efficiency of Alvarado Score (AS) in diagnosis of acute appendicitis.
Keywords: Acute Appendicitis; Alvarado Score; Abdominal Pain.